2003
DOI: 10.1210/jc.2002-021365
|View full text |Cite
|
Sign up to set email alerts
|

Positive Predictive Value of Serum Thyroglobulin Levels, Measured during the First Year of Follow-Up after Thyroid Hormone Withdrawal, in Thyroid Cancer Patients

Abstract: The follow-up of patients with papillary and follicular thyroid carcinoma after thyroidectomy and radioiodine ablation is mainly based on serum thyroglobulin (Tg) level deter-mination. The positive predictive value (PPV) of serum Tg level after thyroid hormone withdrawal, measured during the first 6-12 months of follow-up (initial off L-T(4) Tg), was studied in 256 consecutive differentiated thyroid cancer patients. All underwent a total thyroidectomy and 3.7 GBq (131)I ablation; 37 patients had an elevated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
118
0
12

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(142 citation statements)
references
References 23 publications
12
118
0
12
Order By: Relevance
“…Also, Lee et al (2013) reported that, when high-dose 131 I remnant ablation is performed after total thyroidectomy, the stimulated Tg measurement and DxWBS that are usually performed 6-12 months after 131 I ablation therapy may be skipped in low-and intermediate-risk patients with postoperative stimulated Tg level of <2ng/ml and negative neck ultrasonography findings. Similarly, Baudin et al (2003) reported that, DxWBS with 131 I has a limited interest for the follow-up of thyroid cancer patients. Whereas, we demonstrated that, in 2 of 55 patients with low risk and Tg level of <2ng/mL DxWBS was scan(+) Tg(-) in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Lee et al (2013) reported that, when high-dose 131 I remnant ablation is performed after total thyroidectomy, the stimulated Tg measurement and DxWBS that are usually performed 6-12 months after 131 I ablation therapy may be skipped in low-and intermediate-risk patients with postoperative stimulated Tg level of <2ng/ml and negative neck ultrasonography findings. Similarly, Baudin et al (2003) reported that, DxWBS with 131 I has a limited interest for the follow-up of thyroid cancer patients. Whereas, we demonstrated that, in 2 of 55 patients with low risk and Tg level of <2ng/mL DxWBS was scan(+) Tg(-) in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Serum thyroglobulin measurements are less sensitive in patients with small cervical lymph node metastases or less differentiated tumor (184,200). A rising unstimulated or stimulated serum thyroglobulin may indicate disease that is likely to become clinically apparent (201,202).…”
Section: What Is the Role Of Serum Thyroglobulin Assays In The Followmentioning
confidence: 99%
“…Este achado se deve ao fato de que o tratamento com iodo pode resultar em um lento processo de morte celular e atrofia do tecido residual, não representando, necessariamente, doença recorrente ou persistente, o que pode evitar tratamentos inapropriados com radioiodo (32). Por outro lado, o achado de níveis de Tg em elevação é preditor de doença, devendo ser tratado (39).…”
Section: Medida Da Tireoglobulina Séricaunclassified
“…Em um estudo com 256 pacientes, realizado por Baudin e cols., a ultrassonografia cervical foi o método mais sensível para detecção de focos de neoplasia naqueles pacientes com Tg positiva (39). Para estes autores, a realização do RCT no final do primeiro ano não teve impacto diagnóstico.…”
Section: Ecografia Da Região Cervicalunclassified